Nonlinear Water-Structure Interaction of Fixed Offshore Platform in Extreme Storm - Azarhoushang, Azin; Nikraz, Hamid (ISOPE, 2010)
In this paper a simplified method for dynamic response of jacket-type offshore structures to extreme environmental load is investigated using existing experience and the procedures available within the industry. Since wave loads on offshore platforms varied with time they produce dynamic effects on structures. An accurate and highly efficient procedure for the random vibration computation of complex engineering structures, known as pseudo excitation method (PEM), has been developed since the 1980s (Hongyan et al, 2004). To illustrate the aforementioned methodology, a jacket type offshore platform in the Persian Gulf has been selected.